The acquisition of science process skills through entrepreneurial physics education in senior secondary schools - Akinbobola, Akinyemi Olufunminiyi; Bada, Abiodun Adekunle (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
The need for the acquisition of science process skills is gaining acceptance in secondary school as a crucial preparatory skill for promoting entrepreneurship. The problem of unemployment is a challenge facing many developing nations, with no exception to the developed nations. In the current study, the effect of the acquisition of science process skills through entrepreneurship education on 125 Nigerian senior secondary school students' achievement and retention in